Multi Organ Dysfunction in Term Neonates with Perinatal Asphyxia - Vemuri, Aditya; Lalwani, Sanjay (Journal of Nepal Paediatric Society, 2016)
Introduction: Multiorgan dysfunction (MOD) is one of the four consensus based criteria for the diagnosis of intrapartum asphyxia. The theoretical concept behind MOD is the diving reflex -conservation of blood flow to vital organs at the cost of non-vital organs. The objective of this study was to assess the patterns of involvement of each major organ/system in term asphyxiated neonates. Material and Methods: This was a hospital based prospective study. Sixty term neonates who had suffered perinatal asphyxia were assessed for central nervous system, kidney, cardiovascular system, gastrointestinal system and liver dysfunction. Results: Out of 60 eligible neonates, 57 (95%) had evidence of at least one organ dysfunction. Cardiovascular system involvement (95%) was most common, followed by renal system (37%), hepatic system (22%), central nervous system and hematological system (20% each) and finally, gastrointestinal tract (8%). Conclusion: MOD is frequently associated with perinatal asphyxia with cardiovascular system being the most commonly affected. J Nepal Paediatr Soc 2015;35(3):307-311.